2023
DOI: 10.1136/svn-2022-002191
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glymphatic system as evidenced by low diffusivity along perivascular spaces is associated with cerebral small vessel disease: a population-based study

Abstract: ObjectiveThis study aims to investigate the associations of glymphatic system with the presence, severity and neuroimaging phenotypes of cerebral small vessel disease (CSVD) in a community-based population.MethodThis report included 2219 community-dwelling people aged 50–75 years who participated in the PolyvasculaR Evaluation for Cognitive Impairment and vaScular Events cohort. The diffusivity along perivascular spaces based on diffusion tensor imaging (DTI-ALPS index) was measured to assess glymphatic pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…In this study, we found that a novel magnetic resonance marker of PVS function (DTI-ALPS) predicted both dementia and cognitive decline over a 5-year follow-up period in patients with CSVD. Many previous studies have shown associations between DTI-ALPS and cognition in CSVD, but these have been largely cross-sectional, 20,30,31 with few longitudinal studies, 21 and cannot determine whether PVS diffusion, as measured on DTI-ALPS, causally contributes to CSVD progression. Our data, demonstrating its predictive ability for dementia over a 5-year follow-up, support a potential causal role in cognitive impairment in CSVD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found that a novel magnetic resonance marker of PVS function (DTI-ALPS) predicted both dementia and cognitive decline over a 5-year follow-up period in patients with CSVD. Many previous studies have shown associations between DTI-ALPS and cognition in CSVD, but these have been largely cross-sectional, 20,30,31 with few longitudinal studies, 21 and cannot determine whether PVS diffusion, as measured on DTI-ALPS, causally contributes to CSVD progression. Our data, demonstrating its predictive ability for dementia over a 5-year follow-up, support a potential causal role in cognitive impairment in CSVD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown DTI-ALPS changes in patients with a variety of neurological diseases, including Alzheimer disease, 17 Parkinson disease, 34 and traumatic brain injury. 35 Many cross-sectional studies have also implicated glymphatic dysfunction assessed by DTI-ALPS in patients with CSVD 18,20 and vascular risk factors 19 and have reported associations with the severity of cognitive impairment in both CSVD and vascular cognitive impairment 30,31 and Alzheimer disease. 36 However, few studies have determined whether DTI-ALPS changes predict future cognitive decline and dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, CSVD burden, leukoaraiosis, and EPVS have been extensively found to be associated with stroke recurrence 22–26 . It is worth noting that the glymphatic system, as a new fluid‐clearance pathway in brain, 27,28 has been recently found to be associated with WMHs, lacunae, cerebral microbleeds, and EPVS in patients with CSVD 29,30 . Therefore, potential connection between glymphatic clearance dysfunction and CSVD may be involved in the recurrence of ESUS.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Additionally, it has been demonstrated that individuals with a lower DTI-ALPS index-interpreted as reduced fluid diffusivity in venous PVS-had larger total cSVD burden, as well as an increased risk of WMH burden, lacunes, and brain atrophy. 40 PVS dysfunction has also been linked to the clinical manifestations of cSVD, such as cognitive impairment and lacunar stroke. Both the number of PVS in the BG 41 and the DTI-ALPS index 42 have been associated with the presence of vascular cognitive impairment.…”
Section: Pvs In Ageing and Cardiovascular Risk Factorsmentioning
confidence: 99%